Sequencing effects of sprint interval training applied before or after regular basketball training on sex-specific physical performance adaptations in young athletes - Tian, L.; Jie, C.; Guo, H. (International Journal of Sports Physiology and Performance, 2025)
Purpose: This study investigated the impact of a 6-week sprint interval training (SIT) program conducted either before or after basketball training with a focus on identifying sex differences in the physical performance adaptations of young basketball players.